1993
DOI: 10.1007/bf00797320
|View full text |Cite
|
Sign up to set email alerts
|

Social functioning as a significant factor in women's help-seeking behaviour during the climacteric period

Abstract: In order to identify the psychosocial factors that lead to the demand for medical care related to the menopause, we carried out a case/control study. A case was defined as a woman who sought gynaecological care due to "menopausal complaints" (n = 85) and a control referred to a woman drawn at random from the general population. The cases showed greater psychiatric morbidity and social dissatisfaction, a lower level of diffused social support and a higher frequency of severe life events and the controls showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
1
4
1
Order By: Relevance
“…This result appears to contradict previous findings reported by Ballinger [13] or Montero et al [14], who confirmed that patients with menopausal symptoms had experienced more undesirable life events than healthy control women. This contradiction of results might be partly explained by various researchers' choice of study subjects.…”
Section: Life Events and Menopausal Symptomscontrasting
confidence: 57%
See 1 more Smart Citation
“…This result appears to contradict previous findings reported by Ballinger [13] or Montero et al [14], who confirmed that patients with menopausal symptoms had experienced more undesirable life events than healthy control women. This contradiction of results might be partly explained by various researchers' choice of study subjects.…”
Section: Life Events and Menopausal Symptomscontrasting
confidence: 57%
“…Using a life event model and a multivariate analysis technique, Greene and Cooke [12] reported that life stress in a normal population of women influenced the severity of menopausal symptoms more significantly than did menopause itself. In addition, two studies confirmed that women who sought treatment for menopausal symptoms had experienced more stressful life events than did healthy women [13,14]. These studies strongly suggest the existence of some association between stress and menopausal symptoms.…”
Section: Introductionsupporting
confidence: 57%
“…Although psychological distress is not a necessary outcome of menopause, it is likely the interaction of psychosocial and physiological factors that determines the impact of menopausal symptoms on a woman's life. In addition to stress and cognitive factors discussed earlier, other research has suggested that physical health (Defey, Storch, Cardozo, Diaz, & Fernandez, 1996), social support (Montero, Ruiz, & Hernandez, 1993), and beliefs about menopause and aging (Hunter, 1993) interact to form a unique experience for each woman. Behavioral (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, stress levels (Swartzman, Edelberg, & Kemmann, 1990;Slade & Amaee, 1995), lack of social support (Montero, 1993), beliefs about menopause (Defey, 1996;Hunter, 1993), prior physical and mental health concerns (Defey, 1996;Hunter, 1993;Montero, 1993), and severity of symptoms (Bernhard, 1993) may play a role in treatment-seeking and symptom experience at this time. These findings underscore a need for psychosocial assessment and intervention.…”
mentioning
confidence: 98%